Development of Cavity Matrix Combustor for Biogas Application - Young Nam Chun; June An (ASEAN Journal of Chemical Engineering, 2022)
The use of conventional fossil fuels has limitations in energy resources and environmental problems such as greenhouse gas, air pollution, etc. Biogas has sustainable and renewable characteristics that can be used as an alternative energy source to alleviate these problems. In this study, we proposed a novel cavity matrix combustor that directly enables the combustion of what is produced in small and medium-sized biogas facilities without separation or purification. We also identified combustion characteristics for changes in air ratio, gas feed rate, biogas ratio, and exhaust gas recirculation rate and proposed optimal operating conditions based on this. The performance test result showed that the cavity matrix combustor is excellent for biogas combustion. The optimal operating conditions for the combustor are: the biogas ratio is 60% of CH4 and 40% of CO2, the air ratio is 1.1, the gas feed rate is 30L/min, and the exhaust gas recirculation rate is 100%. At this time, the combustion efficiency was 87%, and the unburned components were CO, UHCs, which are 0.01% and 0.05%, respectively, and NOx was 1ppm.